2014
DOI: 10.3389/fcimb.2014.00071
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and molecular evaluation of Chlamydia trachomatis growth in human endocervix reveals distinct growth patterns

Abstract: In vitro models of Chlamydia trachomatis growth have long been studied to predict growth in vivo. Alternative or persistent growth modes in vitro have been shown to occur under the influence of numerous stressors but have not been studied in vivo. Here, we report the development of methods for sampling human infections from the endocervix in a manner that permits a multifaceted analysis of the bacteria, host and the endocervical environment. Our approach permits evaluating total bacterial load, transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 62 publications
3
79
1
Order By: Relevance
“…There are studies that have presented evidence of C. trachomatis DNA or antigens being present in the tubal material of women with tubal infertility or ectopic pregnancy or salpingitis, supporting the idea that organism persistence in some form occurs in vivo (127,(134)(135)(136). Recently, morphologies consistent with laboratory models of persistence were observed in endocervix samples associated with IFN-␥, further supporting the likely in vivo relevance of laboratory models of persistence (55). It is difficult to determine if chlamydial persistence leading to pathology has always occurred.…”
Section: Ascensionmentioning
confidence: 60%
See 1 more Smart Citation
“…There are studies that have presented evidence of C. trachomatis DNA or antigens being present in the tubal material of women with tubal infertility or ectopic pregnancy or salpingitis, supporting the idea that organism persistence in some form occurs in vivo (127,(134)(135)(136). Recently, morphologies consistent with laboratory models of persistence were observed in endocervix samples associated with IFN-␥, further supporting the likely in vivo relevance of laboratory models of persistence (55). It is difficult to determine if chlamydial persistence leading to pathology has always occurred.…”
Section: Ascensionmentioning
confidence: 60%
“…While ectopic pregnancy is not only a Chlamydia-related pathology, a study by Balasubramaniam et al that found that levels of the cytokines IL-8 and IL-6 were significantly upregulated in the fallopian tubes immediately at the location of implantation of ectopic pregnancy but not in the fallopian tubes of women undergoing benign hysterectomy (54). A very recent study found that differences in IFN-␥ levels correlated with differences in the chlamydial cellular morphologies at the cervix when comparing two patients (55). In summary, the consistent findings of these studies are that IFN-␥, IL-6, IL-1, IL-8, and high antibody responses to some antigens are associated with chlamydial responses in the reproductive tracts of infertile women and Chlamydia-infected women (a notable caveat being that much of the evidence is from uncomplicated infections).…”
Section: Immune Responses From Reproductive Sites and Tissuesmentioning
confidence: 99%
“…(25,(28)(29)(30). Moreover, indole can be detected in vaginal secretions from women with BV and aberrant RBs were observed in cervical scrapings from one patient with C. trachomatis (3). This specimen produced few infectious EBs but contained a high Chlamydia genome load, suggesting that most of the genomes corresponded to persistent organisms (3).…”
mentioning
confidence: 99%
“…Maturing RBs then redifferentiate back to EBs and exit the host cell via lysis or extrusion (2). Morphologically aberrant RBs have been observed in clinical specimens (3). This abnormal developmental cycle can be recapitulated in a laboratory setting by exposing C. trachomatis to various stressors such as host cytokines (4)(5)(6), excess amino acids (7), iron deficiency (8,9), virus coinfections (10), and antibiotics (11,12) (reviewed in reference 13).…”
mentioning
confidence: 99%
“…Persistence in vitro can be induced in cell culture by a variety of methods, including interferon gamma (IFN-␥) treatment of infected human host cells (14), iron starvation via chelation (15,16), and amino acid starvation (17)(18)(19). Of these, IFN-␥-mediated persistence is the most studied and likely the most relevant to in vivo infections (20). The means by which IFN-␥ induces persistence in Chlamydia is well characterized (14,21,22).…”
mentioning
confidence: 99%